Inequalities in access to HIV and syphilis tests in prenatal care in Brazil - Claudia Helena Soares de Morais Freitas; Franklin Delano Soares Forte; Maria Helena Rodrigues Galvão; Ardigleusa Alves Coelho; Angelo Giuseppe Roncalli; Sonia Maria Ferreira Dias
This study aims to evaluate the social determinants of access to HIV and VDRL tests during pregnancy in Brazil. The dependent variables were based on prenatal care access: prenatal care appointments, no HIV and syphilis tests. The independent variables at the first level were formal education level, age, race, work and participation in the Family Income program conditional cash transfer program. The city-level variables were the human development index (HDI), Gini index, and indicators related to health services. An exploratory analysis was performed assessing the effect of each level through prevalence ratios (PR) calculation. A multilevel mixed-effect Poisson regression model was constructed for all outcomes to verify the effect of individual level and with both the individual and contextual levels. Regarding prenatal appointments, the main implicated factors were related to individual socioeconomic position (education level and participation in the Family Income Program conditional cash transfer program), however only HDI maintained significance for the city-level context. The city-level variance dropped from 0.049 to 0.042, indicating an important between-city effect. Regarding the outcomes performing tests in prenatal care, the worst conditions such as contextual (HDI > 0.694, p < 0.001; Gini index ≥ 0.521, p < 0.001) and individual (> 8 years of schooling, p < 0.001) showed a risk effect in the final model. Variables related to health services did not show significant effects. They were associated with individual socioeconomic position and a city-level contextual effect. These findings indicate the importance of strengthening HIV and syphilis infection control programs during pregnancy.